Speech Acts in English Translation of The Holy Qur’an Surah Al-Kahfi By Abdullah Yusuf Ali - Susri, Gusan; Ansar, Fithrah Auliya; Muhassin, Moh (Universitas Islam Negeri Raden Intan Lampung, 2020)
The most iconic study of pragmatics is speech acts, it is understood as the actions which are expressed by utterances. The objective of this research is to identify kinds of speech acts and also speech function (based on Searle category) in the English translation of the Holy Qur'an Surah Al-Kahfi by Abdullah Ali. This research used a qualitative approach. The population consisted of 110 interpretation texts of Surah Al-Kahfi, with nine samples taken as the data of the research chosen by using a purposive sampling technique. There are some steps in analyzing the data. They are: (i) Reading the entire English Interpretation of the Holy Qur'an Surah Al-Kahfi by Abdullah Yusuf Ali, (ii) Identifying the data in situation context, kinds of speech acts, and also speech function based on Searle category, (iii) Concluding the data which have been collected. The result of the research has some points. They are: (i) There are 9 verses which have kinds of speech acts phenomena, it involves locutionary, illocutionary, perlocutionary (ii) Those illocutionary acts involve assertive (stating, boasting), directive (recommending, requesting, advising, commanding). It is possibly engaging another issue on the meaning of translation in the pragmatics view (such as deixis, entailment, reference, implicature, presupposition) or another subject (Surah).